(untitled) (International Seven Journal of Health Research, 2024)
Introduction: Gallbladder cancer (GC) is considered a malignant neoplasm that affects the bile ducts, being a rare and often lethal condition. This pathology represents a challenge in both diagnosis and treatment, this is due to patients usually being asymptomatic or presenting with nonspecific symptoms. Thus, most cases of GC are incidental findings, without previous diagnosis, in patients undergoing cholecystectomy for cholelithiasis. The definitive treatment considered the gold standard for GC is laparoscopic surgery, with removal of the gallbladder (cholecystectomy). The good results of the procedure are dependent on the neoplasm-free hepatic margin and adequate regional lymphadenectomy. Objective: To highlight the importance of adequate treatment for GC, since the improvement of the disease depends on the good results of the procedure. Methods: From a medical case that occurred at the Santa Casa da Misericórdia de Presidente Prudente, and its medical records, information was collected to carry out this report. Results: GC is considered a malignant neoplasm that represents a challenge in both diagnosis and treatment, as patients are usually asymptomatic or have nonspecific symptoms. The definitive treatment considered the gold standard for GC is laparoscopic surgery, with removal of the gallbladder (cholecystectomy). Conclusion: It was evident that it is necessary for a better understanding of the pathology, in addition to studies on the behavior of the GC and its identification in the profile of Brazilian individuals. This type of study would enable prevention, screening, and the adoption of an effective therapeutic indication.